Longing for (a Taiwanese) academy: practical theology as an essentially hospitable and balanced discipline - Chen, Steven K. (2024)
This article argues for two things: the methodology of practical theology and its academic institutions intrinsically embody the concept of hospitality, and the Chinese principle of balance may enhance this understanding. The article begins with a personal reflection on the necessity of a Taiwanese practical theology academy and considers the encouragement received from the Asia Academy of Practical Theology Hong Kong (AAPTHK). It reconsiders the bridge metaphor of practical theology, suggesting a supplementary metaphor drawn from hospitality traditions – the interplay between the roles of host and guest. The article then introduces the Chinese cultural notion of balance to support this new metaphor and avoid some criticisms against intentional hospitality. This notion of balance is then applied as an interpretation tool to understand the dual ‘turns’ in practical theology methodology and the pastoral cycle, demonstrating how various cycle adaptations aim to maintain balance. Ultimately, the discussion culminates in a new vision for a future Taiwanese practical theology academy which is grounded in the principles of balance and hospitality.
Keywords: Academy; host and guest; Hospitality; pastoral cycle; Balance; Chinese culture